Rating the Audience The Business of Media - Balnaves, Mark (Bloomsbury Academic, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Knowing, measuring and understanding media audiences have become a multi-billion dollar business. But the convention that underpins that business, audience ratings, is in crisis. Rating the Audience is the first book to show why and how audience ratings research became a convention, an agreement, and the first to interrogate the ways that agreement is now under threat. Taking a historical approach, the book looks at the evolution of audience ratings and the survey industry. It goes on to analyse today's media environment, looking at the role of the internet and the increased difficulties it presents for measuring audiences. The book covers all the major players and controversies, such as Facebook's privacy rulings and Google's alliance with Nielsen. Offering the first real comparative study, it will be critical for media students and professionals.